Systemic unity of state power - the state power - Ладиченко, Віктор Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article is examined as a constitutional category in the trinity of social cohesion, and the unity of the principal objectives and activities of all government agencies, organizational and legal unity.